Paul's Online Notes
Paul's Online Notes
Home / Calculus I / Derivatives / Implicit Differentiation
Show Mobile Notice Show All Notes Hide All Notes
Mobile Notice
You appear to be on a device with a "narrow" screen width (i.e. you are probably on a mobile phone). Due to the nature of the mathematics on this site it is best views in landscape mode. If your device is not in landscape mode many of the equations will run off the side of your device (should be able to scroll to see them) and some of the menu items will be cut off due to the narrow screen width.

Section 3.10 : Implicit Differentiation

10. Find the equation of the tangent line to \({x^4} + {y^2} = 3\) at \(\left( {1, - \sqrt 2 } \right)\).

Show All Steps Hide All Steps

Hint : We know how to compute the slope of tangent lines and with implicit differentiation that shouldn’t be too hard at this point.
Start Solution

The first thing to do is use implicit differentiation to find \(y'\) for this function.

\[4{x^3} + 2y\,y' = 0\hspace{0.25in}\, \Rightarrow \hspace{0.25in}\,\,\,\underline {y' = - \frac{{2{x^3}}}{y}} \] Show Step 2

Evaluating the derivative at the point in question to get the slope of the tangent line gives,

\[m = {\left. {y'} \right|_{x = 1,\,\,y = - \sqrt 2 }} = - \frac{2}{{ - \sqrt 2 }} = \sqrt 2 \] Show Step 3

Now, we just need to write down the equation of the tangent line.

\[y - \left( { - \sqrt 2 } \right) = \sqrt 2 \left( {x - 1} \right)\hspace{0.25in}\, \Rightarrow \hspace{0.25in}\,\,\,\,y = \sqrt 2 \left( {x - 1} \right) - \sqrt 2 = \require{bbox} \bbox[2pt,border:1px solid black]{{\sqrt 2 \left( {x - 2} \right)}}\]